The Star, 27 April 2007 (Star Publications (Malaysia) Berhad, 2007)
Royal court dances Gamelan Ayak-ayk and Layanng Mas will be showcased at a cultural event at Dataran Merdeka here tomorrow in cunjungtion with the instilation